Investigation on microstructure and morphology of copper alloy castings - M., Nasuha; M. M., Rashidi; A., Hadi; Z., Shayfull (AIP Publishing, 2021)
Todays, there are various of copper alloy specification and application that have been studied by many researchers in order to find the appropriate combination of processing parameters setting in metal casting process. From the previous literatures, the alloy microstructure has been proven will improve the molten part quality. In this study, the application of metal casting of automotive part has been explored. By preparing element composition during melting stages as the variable parameters, investigation of its effect on microstructure was approached. Specimen was selected, cut, prepared and investigate by optical and scanning electron microscope. Based on the results, the alloy morphology is a dendritic structure. The fracture surface also reveals inter-granular fracture between the dendritic structure and its grain boundaries.